Efficacy and safety of different doses of epidural morphine coadministered with low-concentration ropivacaine after cesarean section: A retrospective cohort study - Sun, Liang; Guan, Shuo; Dou, Dou; Feng, Yi; Zhang, Hong; An, Haiyan (Frontiers in Pharmacology, 2023)
Objective: The optimal dose of epidural morphine after cesarean section (CS) still remains unknown when combined with low-concentration ropivacaine based on a continuous basal infusion (CBI) mode. The aim of this study was to assess the impact of different dose of epidural morphine plus ropivacaine on maternal outcomes. Materials and Methods: Data of parturients who received epidural analgesia for CS at a teaching hospital from March 2021 to June 2022 were retrospectively collected. Parturients were divided into two groups (RM3 group and RM6 group) according to different medication regimens of morphine. The implementation of epidural analgesia was performed with 3 mg morphine in RM3 group and 6 mg morphine in RM6 group in combination with 0.1 % ropivacaine via a CBI pump. The primary outcome included pain intensity at rest and movement and the incidence of urinary retention and pruritus within postoperative 48 h. The secondary outcome included the incidence and severity of postoperative nausea and vomiting (PONV), the rate of rescue analgesia and grading of motor Block. Results: Totally, 531 parturients were eligible for the final analysis, with 428 and 103 parturients in the RM3 group and RM6 group, respectively. There were no statistically significant differences in the visual analogue scores (VAS) at rest and movement within postoperative 48 h between the two groups (all P>0.05). Compared with the RM6 group, the incidence of urinary retention was lower in the RM3 group within 48 h after CS (4.0%vs 8.7%, P=0.044). No significant difference was found in the incidence and severity of PONV, the rate of rescue analgesia and grading of motor block between RM3 and RM6 groups. Conclusion: Epidural 3 mg morphine plus 0.1 % ropivacaine in a CBI mode can provide equal efficacy and have lower incidence of urinary retention compared with 6 mg morphine after CS.